What Does the Talking?: Quorum Sensing Signalling Genes Discovered in a Bacteriophage Genome - Hargreaves, Katherine R.; Kropinski, Andrew M.; Clokie, Martha R. J. (PloS one, 2014)
The transfer of novel genetic material into the genomes of bacterial viruses (phages) has been widely documented in several host-phage systems. Bacterial genes are incorporated into the phage genome and, if retained, subsequently evolve within them. The expression of these phage genes can subvert or bolster bacterial processes, including altering bacterial pathogenicity. The phage phiCDHM1 infects Clostridium difficile, a pathogenic bacterium that causes nosocomial infections and is associated with antibiotic treatment. Genome sequencing and annotation of phiCDHM1 shows that despite being closely related to other C. difficile myoviruses, it has several genes that have not been previously reported in any phage genomes. Notably, these include three homologs of bacterial genes from the accessory gene regulator (agr) quorum sensing (QS) system. These are; a pre-peptide (AgrD) of an autoinducing peptide (AIP), an enzyme which processes the pre-peptide (AgrB) and a histidine kinase (AgrC) that detects the AIP to activate a response regulator. Phylogenetic analysis of the phage and C. difficile agr genes revealed that there are three types of agr loci in this species. We propose that the phage genes belonging to a third type, agr3, and have been horizontally transferred from the host. AgrB and AgrC are transcribed during the infection of two different strains. In addition, the phage agrC appears not to be confined to the phiCDHM1 genome as it was detected in genetically distinct C. difficile strains. The discovery of QS gene homologs in a phage genome presents a novel way in which phages could influence their bacterial hosts, or neighbouring bacterial populations. This is the first time that these QS genes have been reported in a phage genome and their distribution both in C. difficile and phage genomes suggests that the agr3 locus undergoes horizontal gene transfer within this species.